2005
DOI: 10.1093/biostatistics/kxi042
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic segmentation and intensity estimation for microarray images

Abstract: We describe a probabilistic approach to simultaneous image segmentation and intensity estimation for complementary DNA microarray experiments. The approach overcomes several limitations of existing methods. In particular, it (a) uses a flexible Markov random field approach to segmentation that allows for a wider range of spot shapes than existing methods, including relatively common 'doughnut-shaped' spots; (b) models the image directly as background plus hybridization intensity, and estimates the two quantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Image analysis is an important application area for HMRFs, the work by Geman and Geman (1984) and Besag (1986) having been influential in this. Recent application areas include micro-array data analysis (Gottardo et al 2006), brain imaging (Smith and Fahrmeir 2007), disease mapping (Green and Richardson 2002) and agricultural field experiments (Besag and Higdon 1999). The Ising model for representing binary lattice data and its generalisation to categorical data, the Potts model, are two well-known and widely applied examples of an MRF-type model.…”
Section: Introductionmentioning
confidence: 99%
“…Image analysis is an important application area for HMRFs, the work by Geman and Geman (1984) and Besag (1986) having been influential in this. Recent application areas include micro-array data analysis (Gottardo et al 2006), brain imaging (Smith and Fahrmeir 2007), disease mapping (Green and Richardson 2002) and agricultural field experiments (Besag and Higdon 1999). The Ising model for representing binary lattice data and its generalisation to categorical data, the Potts model, are two well-known and widely applied examples of an MRF-type model.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that segmentation methods can significantly influence microarray data precision (Ahmed et al, 2004). Successful work on spot location and segmentation has already been done during the last years (Chen et al, 1997;Steinfath et al, 2001;Bozinov and Rahnenführer J, 2002;Yang et al, 2002;Demirkaya et al, 2005;Gottardo et al, 2006). A comparative evaluation of performance can be found in (Lehmussola et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the correlation statistics is useful in flagging low-intensity spots, this method can perform well only on good-quality images. Gottardo et al [25] has applied a Markov random field approach to segmentation. In their method the red and green intensities for both foreground and background were represented using an uncorrelated bivariate t distribution.…”
Section: Introductionmentioning
confidence: 99%